Structural Characteristics of The Semanggol Formation Along The East-West Highway Route 67 Baling Area, Kedah, Malaysia - Ulfa, Yuniarti; Hafizzy , Mohd Hafiz; Farhan, Muhammad (BRIN Publishing, 2012)
The amounts of structural data available from the East-West Highway Route 67 of Baling Area have been used to unravel the structural characteristics of the Semanggol Formation, which comprises black mudstone, sandstone, tuffaceous sandstone, tuff, paraconglomerate, siliceous shale and chert. The area was cut by two sets of faults trending NW-SE and NE-SW. The main fault in this area is known as Bok Bak fault that is trending NW-SE and have moderately to steeply dips (40o-88o) as compared to the conjugate faults. Two sets of folds trending NE-SW and NW-SE were also identified in this area, where most of them are symmetrical fold with gentle to open fold varies from non-plunging to nearly moderately plunging folds. Most of the faults have parallel orientation to the fold axis, indicated this pattern probably originated at the same period of deformation due to warping and uplifting.